Relative Efficacy of Some Insecticides Against the Sucking Insect Pest Complex of Cotton - Asif, M. U.; Muhammad, R.; Akber, W.; Tofique, M. (The Nucleus, 2017)
The comparative efficacy of some conventional and neonicotinoid insecticides for the management of sucking insect pests of cotton (whitefly, jassid and thrips) was determined. Six insecticides viz., Confidor 200 SL (imidacloprid)@ 100 ml acre-1, Karate 1.5 EC (lambda cyhalothrin)@ 330 ml acre-1, Nockout 25 SP (nitenpyram)@ 100 gm acre-1, Polytrin-C 44 EC (profenofos+cypermethrin)@ 600 ml acre-1, Talstar 10 EC (bifenthrin)@ 250 ml acre-1 and Advantage 20 EC (carbosulfan)@ 1000 ml acre-1 were sprayed twice in order to ascertain the reduction of the pests population on Sadori variety of cotton sown at experimental area of Nuclear Institute of Agriculture, Tandojam. All the tested insecticides caused significant reduction of whitefly, jassid and thrips at 24 hours, 72 hours and even 7 days after application. Imidacloprid followed by the nitenpyram proved to be most effective for bringing about a significant reduction in the populations of whitefly and thrips. Nitenpyram had the highest percentage reduction (73.80%) against jassid at 7th day after application but that was non-significantly different from imidacloprid(63.49%).Whereas, the conventional insecticides i.e. lambda cyhalothrin, profenofos+cypermethrin, bifenthrin and carbosulfan showed 57.93%, 52.38%, 47.61% and 42.06% reduction, respectively. Maximum extrapolated yield (2.99 tons ha-1) was also obtained in imidacloprid treated plots followed by nitenpyram (2.66 tons ha-1). Thus, these two insecticides were most effective for the sucking pests and in increasing seed cotton yield as compared to the conventional ones.